Ex vivo model for studying polymicrobial biofilm formation in root canals - Díez Ortega, Hugo; Infectious Diseases Group, School of Sciences, Department of Microbiology, Pontificia Universidad Javeriana. Bogotá, Colombia. (2017)
Endodontic disease has mainly a microbial origin. It is caused by biofilms capable of attaching and surviving in the root canal. Therefore, it is important to study the conditions in which those biofilms grow, develop and colonize the root canal system. However, few studies have used natural teeth as models, which would take into account the root canal anatomical complexity and simulate the clinical reality. In this study, we used human premolar root canals to standardize in vitro biofilm optimal formation conditions for microorganisms such as Enterococcus faecalis, Staphylococcus aureus and Candida albicans. 128 lower premolars underwent canal preparation using K-type files, and were treated with 5.25% sodium hypochlorite and EDTA. Samples were inoculated with microorganisms and incubated for 15, 30, 45, and 60 days under anaerobiosis (CO2 atmosphere) and aerobiosis. Microorganism presence was confirmed by Gram staining, cell culture, and electron microscopy. Exopolysaccharide matrix and microorganism aggregation were observed following 15 days of incubation. Bacterial growth towards the apical third of the root canal and biofilm maturation was detected after 30 days. CO2 atmosphere favored microbial growth the most. In vitro biofilm maturation was confirmed after 30 days of incubation under a CO2 atmosphere for both bacteria and yeast.